First-principles study of cohesion strength and stability of titanium–carbon interfaces using vdW interaction. (8th January 2020) - Chen, Liang; Luo, Junming; Wang, Qian; Xiong, Lei; Gong, Haoran
Abstract: Interface adhesion and stability between titanium and carbon materials have been investigated by first-principles calculation, in which three different DFT-PBE, DFT-LDA and optB88-vdW approaches are considered. Our calculation reveals that the formation of carbon vacancy in graphene would enhance the interface stability and increase interfacial strength, which may be due to a strong hybridization between titanium atom and the sp 2 dangling bonds of the carbons near the vacancy. It is also found that the van der Waals interaction has less effects on cohesion properties of the titanium/graphite interfaces, and the Ti-C bond of titanium–carbon interfaces is weaker than that of the TiC bulk. The derived results are discussed in depth by means of electron distribution and Bader transfer analysis, and could be used as a guiding parameter for exploring the fundamental properties of titanium–carbon products as well as various potential applications.